Analisis Pemilihan Supplier Dalam Pengadaan Material Kapur Menggunakan Analytical Hierarchy Process (Studi Kasus PT. Aneka Jasa Grhadika) - Evie Talia Nurrohmah; Yanuar Pandu Negoro; Moh. Jufriyanto (Jurnal Serambi Engineering, 2023)
PT Aneka Jasa Grhadika is a company that focuses on the Engineering, Procurement, and Construction (EPC) sector. They are highly committed to maintaining the quality of their products with the aim of providing trust and satisfaction to customers. To manufacture its products, the company adopts three main production systems, namely Make to Order (MTO), Assembly to Order (ATO), and Engineering to Order (ETO). They are very committed to maintaining the quality of their products with the aim of providing trust and satisfaction to customers. The purpose of this study is to formulate the right decision in the context of selecting the best supplier for PT Aneka Jasa Grhadika, which has previously been one of their suppliers. The method applied is the Analytical Hierarchy Process (AHP), a decision-making technique that generates priorities for alternatives when multiple criteria are considered. Therefore, in the decision-making process, decision-makers must transform complex problems into a unified hierarchy of several levels. The results showed that the quality criteria received a weight of 32.5%. The price criteria received a weight of 31.3%, the flexibility criteria received a weight of 15.3%, the delivery criteria received a weight of 10.6% and the service criteria received a weight of 10.3%. In this study, there are three supplier options that can be selected. The analysis results show that PT Timbul Persada has a weight of 39.3%, PT Nafaro Bumi Mandiri has a weight of 37.8%, while supplier PT Harang Bumi Energi has a weight of 22.9%.